Effect of Diabetes Induction and Exercisetraining on the Level of Ascorbic Acid and Muscle SVCT2 in Male Wistar Rats - Akbar Ghalavand; Pezhman Motamedi; Hamid Rajabi; Neda Khaledi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2019)
Introduction: Sodium-dependent vitamin C transporter 2 (SVCT2) plays an important role in the transfer of ascorbic acid to slow-twitch fiber. The purpose of this study was investigating the effect of diabetes induction and exercise training on the level of ascorbic acid and muscle SVCT2 in rats. Methods: In this experimental study, 20 male Wistar rats were randomly divided into four groups (n=5 per group): 1) healthy control 2) diabetic control, 3) diabetic exercise, 4) sham. Diabetic was induced by injection of Streptozotocin solution (55 mg / kg). The exercise program was performed 6 weeks of aerobic running on Treadmill, 5 sessions per week and each training session for 20-40 minutes at an intensity of 50-70% VO2max. Homogeneous tissue of soleus muscle and serum was analyzed to evaluate the effect of exercise training on ascorbic acid metabolism. Data were analyzed by SPSS version 18 software and one-wayANOVA test (P ≤ 0.05). Results: The results showed that there was significant differences (P < 0.05) between the level muscle and serum ascorbic acid in diabetic and diabetic + exercise groups compare to the healthy control and sham groups. But no significant differences was found in SVCT2 of Soleus muscle between groups (P> 0.05). Conclusion: Induction of diabetes induces a decrease in muscle levels of ascorbic acid, which appears to be associated with a decrease in serum ascorbic acid levels, since no significant difference was found in SVCT2 levels. Also, exercise training had no significant effect on serum and muscle ascorbic acid levels of muscle SVCT2 levels.